The Use of Motivational Interviewing (Mi) in Preventing Relapse on Methamphetamine Drug User - Nazlan Ibrahim; Mohamad Isa Amat; Abdul Rashid Abdul Aziz (USIM Press, 2024)
Vol. 25 No. 2 (2021): Special Issue MASEC